PREVALENCE OF BURNOUT AND FATIGUE AMONG HEALTHCARE WORKERS OF A SECONDARY HEALTHCARE INSTITUTION IN BELGRADE DURING THE SARS-COV-2 PANDEMIC - Giljača, Sonja (Acta medicae Medianae, 2026)
Burnout has been recognized increasingly globally as a major concern, affecting the physical and mental well-being of Healthcare Workers (HCWs). A cross-sectional study was conducted among the healthcare workers in Special Hospital for Rehabilitation and Orthopedic Prosthetics using the following questionnaires: Maslach Burnout Inventory–Human Services Survey (MBI–HSS) for measuring the three aspects of burnout syndrome: emotional exhaustion (EE), depersonalization (DP), and personal accomplishment (PA); Fatigue Severity Scale (FSS) for assessing the presence and degree of fatigue, and sociodemographic characteristics of respondents collected through a general questionnaire. Only fully completed questionnaires, 65 of the total of 79, were included in the study. The majority of participants were females (73.8%), married (61.5%), university degree holders (52.3%), homeowners (66.2%), and those earning above the minimum (81.5%). One third of study participants experienced the death of a close person due to coronavirus disease 2019 (COVID-19). High level of EE was observed in 41.5% of employees. Moderate to high level of DP was recorded in 36.9% of participants, and 40% exhibited a low level of PA. Emotional exhaustion was positively correlated with the FSS. Depersonalization showed a statistically significant positive correlation with the FSS. The length of vacation as the demographic characteristic was also positively correlated with the FSS. Two factors were found to be associated with high levels of EE among HCWs, and those were higher fatigue and lower monthly earnings.